P‐4.4: A design to improve the uniformity of AMOLED panel. (4th October 2019) - Zhang, Liuqi; Han, Baixiang; Chaw, Gary; Lin, Xinnan
Abstract : In this paper, we have proposed a method to improve the uniformity of our panel display. Through the small angle of gate signal, we have successfully improved the feedthrough status of different areas on the panel, and increased the nine‐point uniformity from 65.9 percent to 90.4 percent in low gray level. Finally, using this timing, we successfully obtained a 31‐inch display with uniform brightness.